PENERAPAN MEDIA RODA PINTAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SANGGAR BIMBINGAN SUNGAI MULIA MALAYSIA - Satria Pratama, Bagas; Kuswandi, Iwan; Armadi , Ali (JS (JURNAL SEKOLAH), 2024)
Abstract: This research was carried out at SBSM 5 Gombak Malaysia on 17-20 September 2024. The initial reading ability of grade 1 students at Sanggar Guidance Sungai Mulia (SBSM) Malaysia is low, so special attention is needed for teachers as educators to improve students' ability to read. The purpose of writing this article is to find out how the teaching and learning process at SBSM Malaysia is in learning Indonesian using the smart reading wheel learning media which is carried out using a qualitative approach with case study research and data sources using observation, interviews and documentation. The data collection process includes data reduction, data presentation, and drawing conclusions. The result of writing this article is that the smart reading wheel media is expected to make it easier for students to recognize letters and spell letters so that they can read word for word. Because of this, researchers are eager to conduct research and create media roda pintar to address the issue at hand through research with the title "Application of Smart Wheel Media to Improve the Beginning Reading Ability of Sanggar Guidance Students at Sungai Mulia Malaysia". Keywords: Media, Beginning Reading, Guidance Studio Abstrak: Penelitian ini dilaksanakan di SBSM 5 Gombak Malaysia pada tanggal 17-20 september 2024. Kemampuan membaca permulaan siswa kelas 1 di Sanggar Bimbingan Sungai Mulia (SBSM) Malaysia yang rendah, maka perlu adanya perhatian khusus bagi guru sebagai pendidik untuk meningkatkan kemampuan siswa dalam membaca. Tujuan dari penulisan artikel ini yaitu untuk mengetahui bagaimana proses belajar mengajar di SBSM Malaysia pada pembelajaran bahasa Indonesia dengan menggukan media pembelajaran roda pintar membaca yang dilaksakan menggukan pendekatan kualitatif dengan jenis penelitian studi kasus dan sumber data menggunakan observasi, wawancara, dan dokumentasi. Proses pengumpulan data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penulisan artikel ini yaitu media roda pintar membaca di harapkan dapat mempermudah siswa dalam mengenal huruf dan mengeja huruf sehingga sampai bisa membaca kata demi kata. Oleh karena itu peneliti bersemangat untuk melakukan penelitian dan membuat media roda pintar untuk menjawab permasalahan yang ada melalui penelitian dengan judul “ Penerapan Media Roda Pintar Untuk Meningkatkan Kemampuuan Membaca Permulaan Siswa Sanggar Bimbingan Sungai Mulia Malaysia”. Kata Kunci: Media, Membaca Permulaan, Sanggar Bimbingan